ACTH-secreting Pancreatic Neoplasms Associated With Cushing Syndrome. (March 2015) - Maragliano, Roberta; Vanoli, Alessandro; Albarello, Luca; Milione, Massimo; Basturk, Olca; Klimstra, David S.; Wachtel, Antonio; Uccella, Silvia; Vicari, Emanuela; Milesi, Marina; Davì, Maria Vittoria; Scarpa, Aldo; et al.
<x xml:space="preserve">Abstract</x> Adrenocorticotropic hormone (ACTH)-secreting pancreatic neuroendocrine tumors (PanNETs), although rare, are responsible for about 15% of ectopic Cushing syndrome (CS). They represent a challenging entity because their preoperatory diagnosis is frequently difficult, and clear-cut morphologic criteria useful to differentiate them from other types of PanNETs have not been defined. Ectopic ACTH secretion associated with CS can also be rarely due to pancreatic acinar cell carcinoma (ACC) and pancreatoblastoma, rare tumor types with morphologic features sometimes overlapping those of PanNETs and, for this reason, representing a diagnostic challenge for pathologists. We herein describe the clinicopathologic and immunohistochemical features of 10 PanNETs and 1 ACC secreting ACTH and associated with CS together with an extensive review of the literature to give the reader a comprehensive overview on ACTH-producing pancreatic neoplasms. ACTH-secreting PanNETs are aggressive neoplasms with an immunohistochemical profile that partially overlaps that of pituitary corticotroph adenomas. They are generally large and well-differentiated neoplasms without distinctive histologic features but with signs of aggressiveness including vascular and perineural invasion. They are more frequent in female individuals with a mean age of 42 years. At 5 and 10 years after diagnosis, 35% and 16.2% of patients, respectively, were alive. ACTH-secreting ACCs and pancreatoblastomas are very aggressive pediatric tumors with a poor prognosis. Using an appropriate immunohistochemical panel including ACTH, β-endorphin, trypsin, and BCL10 it is possible to recognize ACTH-secreting PanNETs and to distinguish them from the very aggressive ACTH-secreting ACCs.